Ethnic intermarriage among immigrants: human capital and assortative mating - Barry R. Chiswick; Christina A. Houseworth (Institute for the Study of Labor (IZA), 2008)
This paper analyzes the determinants of interethnic marriages among immigrants in the United States. The dependent variable is intermarriage across ethnic groups and the inclusion of the explanatory variables is justified by a simple rational choice economic model. A binomial logistic regression is estimated using data from the 1980 US Census, the last Census where post-migration marriages can be identified. Results show that the probability of intermarriage increases the longer a migrant resides in the U.S. and the younger the age at arrival. Both relationships can be attributable to the accumulation of US-specific human capital and an erosion of ethnic-specific human capital. Inter-ethnic marriages are more likely between individuals with similar education levels, providing evidence of positive assortative mating by education for immigrants. Construction of the availability ratio for potential spouses and group size are unique to this study, providing a more accurate measure of the marriage market by using data from several Censuses. Intermarriage is lower the greater the availability ratio and the larger the size of the group. Linguistic distance indirectly measures the effect of English language ability at arrival and is found to be a significant negative predictor of intermarriage. Those who report multiple ancestries and who were previously married are more likely to intermarry.
urn:nbn:de:101:1-2008101552
Keywords: J12; 330; Immigrants; marriage; ethnicity/ancestry; Ehe; Ethnische Beziehungen; Migranten; Bildungsniveau; Englisch (Sprache); USA